Розрахунки та проектування машинобудівних конструкцій за допомогою інтернет-сайту "марочник сталей і сплавів" - Бреславська, Олена Олександрівна; Іщук, Ю. О. (НТУ "ХПІ", 2006)
The paper is devoted to the procedure of using the specialized Internet-site made for organization, saving, quick access and data processing of metal properties in the design and calculation of engineering structures
Keywords: Internet-технології; металургійна галузь; коефіцієнт теплопровідності; питомий електричний опір